IMPORTANCE OF REPEATED SHODHANA IN KITIBHA KUSHTA (PSORIASIS) A CASE STUDY - Sneha Patil; Prashanth Bhat (International Journal of Ayurveda and Pharma Research, 2021)
Introduction: Skin conditions adversely affect one’s physical and emotional well-being, thereby causing negative impact on one’s own quality of life. In Ayurveda Kushta is the term used to denote different varieties of skin diseases, which includes all major skin manifestations such as Psoriasis. Kitibha kushta is one among Kshudra kushta with predominance of vitiated Vata-Kapha dosha. The clinical features are: Shyava, Kina-Kara sparsha and Parushata, which can be co-related to Psoriasis. Psoriasis is a commonly encountered chronic skin disease, regularly encountered in day-to- day clinical practice with prevalence of 2% worldwide. Methodology: The present case report is of 26 years old female, came with complaints of Scaly Patchy discoloration all over the body predominantly over Extensor surface of both limbs and face with dry crusty flakes over scalp margins associated with Itching and Blood discharge on scratching and was effectively treated with Shodhana. Result: Patient showed encouraging result after repeated Shodhana followed by Shamana aushadis. Discussion: Patient was Initially treated with Virechana, were the flare up of the condition was observed, later treated with repeated course of Vamana followed by Virechana in regular intervals, where she was observed with 75% of relief with no further episodes of recurrence. Hence, the present case study highlights the importance of repeated Shodhana (Vamana, Virechana) as mentioned in classics for the management of Kitibha Kushta.